Characterization and source apportionment of polycyclic aromatic hydrocarbons (pahs) in the sediments of gulf of Pozzuoli (Campania, Italy). Issue 1 (15th November 2017) - Arienzo, Michele; Donadio, Carlo; Mangoni, Olga; Bolinesi, Francesco; Stanislao, Corrado; Trifuoggi, Marco; Toscanesi, Maria; Di Natale, Gabriella; Ferrara, Luciano
Abstract: Most of the literature reports on the impact of the former Bagnoli brownfield on the pollution of Bagnoli Bay, embedded in the Gulf of Pozzuoli (GoP). Thus, we studied concentrations, types and sources of sixteen PAHs (EPA) in sediments at 22 sites along 5 transects covering the entire area of GoP. Outstanding levels of PAHs were found, varying from 7.1 μg g − 1 to 2.5 E + 3 μg g − 1 . Sediments collected at sites far away from Bagnoli were found to be polluted to a similar extent than those facing the brownfield site, with values > 100 μg g − 1 . Total PAHs levels in the sediments of GoP were higher by thirty-eleven thousand fold than those reported by other studies from various marine sites in the world. Transit axes of fine and very fine sands and diagnostic indexes revealed a common pyrolytic PAHs pollution spreading from the Bagnoli plant to all GoP. Highlights: Mapping of Polycyclic Aromatic Hydrocarbons and sources in the Gulf of Pozzuoli Twelve diagnostic indexes for attribution of PAHs emission source Determination of sedimentary transit axes along the seabed by grain size analysis Outstanding levels of PAHs pollution over all the Bay of Pozzuoli Pyrogenic nature of PAHs from Bagnoli brownfield through all Pozzuoli Gulf